REPRESENTASI ORANG TUA DALAM PENDIDIKAN AKHLAK REMAJA - Susila, Elis Ela; Putri, Septiani; wardi, Suhro (THORIQOTUNA: Jurnal Pendidikan Islam, 2022)
The study aims to determine the effect of parental concern for religious education on adolescent morals in RW O4 Mandalare Village, Mandalare Villlage, Panjalu District, Ciamis Regency. The method used in this research is descriptive through a quantitative approach, namely research that seeks to reveal the conditions that occur at the present time by considering past conditions through processing the numbers obtained from the research. Based on the results of data processing, it was found that the influence of parental care in religious education on adolescent morals in RW 04 Mandalare Village, Mandalare Village, Panjalu District, Ciamis Regency had a significant positive effect with sufficient category, it was proven that rs = 0.49 interval 0.41-0.60 and thime (5,194) table (1,664). Parental concern affects adolescent morals by 24.01%, while the remaining 75.99% is throught to be determined by other factors.